2021
DOI: 10.1038/s41598-021-81831-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety, biodistribution and viral shedding of oncolytic vaccinia virus TG6002 administered intravenously in healthy beagle dogs

Abstract: Oncolytic virotherapy is an emerging strategy that uses replication-competent viruses to kill tumor cells. We have reported the oncolytic effects of TG6002, a recombinant oncolytic vaccinia virus, in preclinical human xenograft models and canine tumor explants. To assess the safety, biodistribution and shedding of TG6002 administered by the intravenous route, we conducted a study in immune-competent healthy dogs. Three dogs each received a single intravenous injection of TG6002 at 105 PFU/kg, 106 PFU/kg or 107… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“… 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Distribution is driven primarily by interactions between the virus and the mononuclear phagocytic system (MPS) via a panoply of nonspecific interactions (e.g., sialic acids) and serum factors (e.g., complement and natural antibodies). 15 , 24 , 31 , 32 , 33 , 34 To date, PK/BD studies of OVs have used various methods for measuring virus replication in vivo (e.g., qRT-PCR, infectivity assays, protein reporters, reporter imaging 35 , 36 , 37 , 38 , 39 , 40 , 41 ), which do not easily discern between the input virus disposition and replication. Furthermore, replication impacts both concentration-time (PK/BD) and concentration-effect (PD) profiles, resulting in a bidirectional relationship between PK and PD, which has been alluded to by others.…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Distribution is driven primarily by interactions between the virus and the mononuclear phagocytic system (MPS) via a panoply of nonspecific interactions (e.g., sialic acids) and serum factors (e.g., complement and natural antibodies). 15 , 24 , 31 , 32 , 33 , 34 To date, PK/BD studies of OVs have used various methods for measuring virus replication in vivo (e.g., qRT-PCR, infectivity assays, protein reporters, reporter imaging 35 , 36 , 37 , 38 , 39 , 40 , 41 ), which do not easily discern between the input virus disposition and replication. Furthermore, replication impacts both concentration-time (PK/BD) and concentration-effect (PD) profiles, resulting in a bidirectional relationship between PK and PD, which has been alluded to by others.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary lymphoid tissue is another common target for the majority of OVs (Figure 2). The increased viral titers in the spleen have been shown for VV, [14][15][16][17][18] VSV, [33][34][35] MG1, 36,37 MV, 39 Ad, 46 reovirus, 28 NDV, 156,157 and for the recently described oncolytic alphavirus M1. 158 Of note, for different viruses, the splenic infection has similar dynamics, reaching a peak within a few hours and gradually decreasing thereafter.…”
Section: Infection In Secondary Lymphoid Tissuesmentioning
confidence: 99%
“…Spleen and liver are the major filters for circulating pathogens and therefore the detection of VV in these organs may simply reflect the sequestration of the injected virus. Nevertheless, several independent studies demonstrate that VV is found more frequently and with higher titers in the spleen than in the liver, [15][16][17][18] indicating that splenocytes may permit viral replication. Although the infected cells have not been identified yet, it is likely that VV specifically targets marginal metallophilic macrophages (MMMs).…”
Section: How Do Ovs Manage To Infect Non-cancer Cells?mentioning
confidence: 99%
See 1 more Smart Citation
“…The TK-deleted vaccinia virus GLV-1h68 (GL-ONC1) harboring β-galactosidase and β-glucuronidase genes has also undergone clinical trials and showed good efficacy in head and neck squamous-cell carcinoma [8]. Moreover, recombinant vaccinia virus TG6002 with deletions of two genes (TK and ribonucleotide) and insertion of the suicide gene FCU1, is currently being eval-uated in clinical trials [9]. In short, oncolytic vaccinia viruses have shown considerable safety and efficacy in clinical trials.…”
Section: Introductionmentioning
confidence: 99%